2020
DOI: 10.1101/2020.03.08.982637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerodynamic Characteristics and RNA Concentration of SARS-CoV-2 Aerosol in Wuhan Hospitals during COVID-19 Outbreak

Abstract: Background:The ongoing outbreak of COVID-19 has spread rapidly and sparked global concern. While the transmission of SARS-CoV-2 through human respiratory droplets and contact with infected persons is clear, the aerosol transmission of SARS-CoV-2 has been little studied.Methods: Thirty-five aerosol samples of three different types (total suspended particle, size segregated and deposition aerosol) were collected in Patient Areas (PAA) and Medical Staff Areas (MSA) of Renmin Hospital of Wuhan University (Renmin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
284
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(313 citation statements)
references
References 9 publications
14
284
0
11
Order By: Relevance
“…Liu et al collected 35 aerosol samples from three areas in two hospitals of Wuhan, and tested 2019-nCoV RNA by droplet digital polymerase chain reaction. 51 They found that patient area had low or even undetectable aerosol 2019-nCoV RNA, but deposition aerosol were tested positive, suggesting that not much vital virus in air flow but tend to deposit to the floor, which is similar to movements of large saliva droplets as noted previously. 51 In medical staff area, airborne 2019-nCoV RNA concentration was decreased after patients reduced and sanitization rigorously implemented.…”
Section: Possible Direct Invasions Into Oral Tissuesmentioning
confidence: 58%
See 3 more Smart Citations
“…Liu et al collected 35 aerosol samples from three areas in two hospitals of Wuhan, and tested 2019-nCoV RNA by droplet digital polymerase chain reaction. 51 They found that patient area had low or even undetectable aerosol 2019-nCoV RNA, but deposition aerosol were tested positive, suggesting that not much vital virus in air flow but tend to deposit to the floor, which is similar to movements of large saliva droplets as noted previously. 51 In medical staff area, airborne 2019-nCoV RNA concentration was decreased after patients reduced and sanitization rigorously implemented.…”
Section: Possible Direct Invasions Into Oral Tissuesmentioning
confidence: 58%
“…51 They found that patient area had low or even undetectable aerosol 2019-nCoV RNA, but deposition aerosol were tested positive, suggesting that not much vital virus in air flow but tend to deposit to the floor, which is similar to movements of large saliva droplets as noted previously. 51 In medical staff area, airborne 2019-nCoV RNA concentration was decreased after patients reduced and sanitization rigorously implemented. 51 In public area, accumulation of crowds increased airborne 2019-nCoV RNA concentration from undateable level.…”
Section: Possible Direct Invasions Into Oral Tissuesmentioning
confidence: 58%
See 2 more Smart Citations
“…At the same time, a number of studies have shown that airborne transmission route could spread viruses even further the close contact with infected people [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Paules et al (2020) highlighted that -besides close distance contacts -airborne transmission of SARS-CoV can also occur [5].…”
Section: Introductionmentioning
confidence: 99%